METHOD OF MENTAL STATE DYNAMIC MODELING ON IMPACT OF MEDICINAL PREPARATIONS - Vladimir Aleksandrovich Utkin; Ivan Mitrofanovich Pershin; Tatyana Valeryevna Kukharova (Современная наука и инновации, 2022)
The sintez of human mental state control system is considered. The mental state evaluated by the human body conductance parameters. Control is performed by medications used to treat mental disorders.